Comparing pore structure models of nanoporous carbons obtained from small angle X-ray scattering and gas adsorption - Prehal, C.; Grätz, S.; Krüner, B.; Thommes, Matthias; Borchardt, L.; Presser, V.; Paris, O. (Carbon, 2019)
The performance of nanoporous carbons, used for hydrogen storage, ionic charge storage, or selective gas separation, is strongly determined by their pore shape and size distribution. Two frequently used experimental techniques to characterize the nanopore structure of carbons are gas adsorption combined with quenched-solid density functional theory and small angle X-ray scattering. However, neither of the two techniques can unambiguously derive a valid pore model for disordered pore structures without making assumptions. Here, we quantitatively compare pore size distributions from X-ray scattering and gas adsorption data. We generate three-dimensional pore models of activated carbons using small angle scattering and the concept of Gaussian Random Fields. These pore models are used to generate pore size distributions inherently containing a slit-pore assumption, making them comparable to pore size distributions obtained from gas adsorption analysis. This is realized by probing the effective adsorption potential via sampling of the three-dimensional pore structure with a probing adsorbate and calculating a “Degree of Confinement” parameter accounting for local pore geometry effects. We also generate pore size distributions with an alternative definition of pore size and discuss intricacies of gas adsorption results, such as the general tendency to underestimate the pore size dispersity in disordered microporous carbons.
CRIS-Team Scopus Importer:2019-06-25